Fleshy seeds form in the basal Angiosperm Magnolia grandiflora and several MADS‐box genes are expressed as fleshy seed tissues develop. Issue 1 (January 2015) - Lovisetto, Alessandro; Masiero, Simona; Rahim, Md Abdur; Mendes, Marta Adelina Miranda; Casadoro, Giorgio
SUMMARY One successful mechanism of seed dispersal in plants involves production of edible fleshy structures which attract frugivorous animals and transfer this task to them. Not only Angiosperms but also Gymnosperms may use the fleshy fruit habit for seed dispersal, and a similar suite of MADS‐box genes may be expressed as these structures form. Magnolia grandiflora produces dry follicles which, at maturity, open to reveal brightly colored fleshy seeds. This species thus also employs endozoochory for seed dispersal, although it produces dry fruits. Molecular analysis reveals that genes involved in softening and color changes are expressed at late stages of seed development, when the fleshy seed sarcotesta softens and accumulates carotenoids. Several MADS‐box genes have also been studied and results highlight the existence of a basic genetic toolkit which may be common to all fleshy fruit‐like structures, independently of their anatomic origin. According to their expression patterns, one of two AGAMOUS genes and the three SEPALLATA genes known so far in Magnolia are of particular interest. Duplication of AGAMOUS already occurs in both Nymphaeales and Magnoliids, although the lack of functional gene analysis prevents comparisons with known duplications in the AGAMOUS lineage of core Eudicots.